Synthesis and Characterization of Cu-Doped Zirconium Titanate as A Potential Visible-Light Responsive Photocatalyst - Katarina Rachma Andita; Rian Kurniawan; Akhmad Syoufian (Indonesian Journal of Chemistry, 2019)
Synthesis and characterization of Cu-doped zirconium titanateas a potential visible-light responsive photocatalyst had been conducted. Titanium tetraisopropoxide (TTIP) was used as a precursor of Ti source, reacted to ZrO2 powderand CuSO4·5H2O with various Cu concentrations of 0, 1, 3, 5, 7 and 9% (w/w) by sol-gel method. Zirconium titanate with Cu concentration of 5% was calcined at various temperatures of 500, 700 and 900 °C. All materials were characterized by using XRD, FTIR, SRUV, and SEM-EDX. The characterization proved that the materials were potential as a model of visible-light responsive photocatalyst. Composite with optimum bandgap energy (Eg) was obtained at 5% Cu content after 500 °C with an absorption edge wavelength of 431.93 nm and the bandgap of 2.87 eV.